Ordinance no. 11-An Ordinance Concerning Offenses and Disorderly Conduct, § 27, Ilwaco Town Council (1891) (Washington). - (:unkn) unknown (My University, 1891)
Any person or persons who shall fire off or discharge any ordinance gun, pistol. rifle or other fire-arms within the Town of Ilwaco shall upon conviction thereof before the Police Court pay a fine of not less than One nor More than One Hundred Dollars. Provided that the Mayor with the consent of the majority of the Committee on Health and Police may permit upon National holidays and other days and other days of public celebration the same which permit shall designate the time and locality of firing.
Keywords: DISCHARGE